Types of Transnasal Endoscopic Nasopharyngectomy for Recurrent Nasopharyngeal Carcinoma: Shanghai EENT Hospital Experience - Liu, Quan; Sun, Xicai; Li, Han; Zhou, Jiaying; Gu, Yurong; Zhao, Weidong; Li, Houyong; Yu, Hongmeng; Wang, Dehui (Frontiers in Oncology, 2021)
Background: Transnasal endoscopic nasopharyngectomy (TEN) has become increasingly used for recurrent nasopharyngeal carcinoma (rNPC); however, there is no report on the definitive resectable contour for TEN according to the latest staging system for nasopharyngeal carcinoma. The aim of this study was to establish the types of TEN for rNPC. Materials and Methods: A total of 101 rNPC patients underwent TEN from January 2016 to April 2019 at the authors’ institution. TEN was categorized into four types, which included type I (n=40) with resection of the nasopharynx and sinuses; type II (n=10) with lateral extension to the parapharyngeal space; type III (n=40) with lateral extension to the floor of the middle cranial fossa and the infratemporal fossa and superior extension to the orbital apex and the cavernous sinus back to the prevertebral region; and type IV (n=11) with the resection of the involved internal carotid artery following type III. The 2-year overall survival rate (OS) and local recurrence-free survival rate (LRFS) were assessed. Results: The median time of follow-up was 20 months. Twenty-five patients reoccurred. Nineteen patients died. Independent predictors of outcome on multivariate analysis were recurrent T stage (P = 0.039), types of TEN (P = 0.002) and surgical margin (P = 0.003). The 2-year OS and LRFS was 76.2% and 53.6%, respectively. Conclusions: The result of TEN in the treatment of rNPC is promising. The types of TEN will provide effective guideline for surgical treatment of rNPC.